A review on evaporation improvement of solar still desalination using porous material. (November 2022) - Shoeibi, Shahin; Saemian, Mohammad; Kargarsharifabad, Hadi; Hosseinzade, Siamak; Rahbar, Nader; Khiadani, Mehdi; Rashidi, Mohammad Mehdi
Abstract: Recently, many studies have focused on desalination systems using solar energy sources due to low energy costs, the feasibility of usage in most weathers and no use of fossil fuels. Different materials have been proposed to enhance the temperature gradient and to gain better water productivity of the system such as porous materials, nanoparticles and phase change materials. Due to the uneven and porous surface, the porous materials raise the solar intensity absorption and the water temperature. This present review article assists to study the implementation of porous materials in evaporation enhancement of solar water desalination systems. All previous studies have demonstrated that the use of porous materials has a significant influence on the evaporation rate in solar desalination systems. Eventually, a summary of comparison in previous publications was presented and discussed in detail to assist researchers and engineers with a better design of solar still desalination systems. The achieved outcomes indicated that the energy efficiency of the solar desalination using activated carbon as a porous media was enhanced by 94.14%. Moreover, the productivity of the solar still desalination by aluminium fins and black steel wool fiber as a porous material was increased by about 42.3% and 20.9%, respectively. Highlights: Porous media increases the evaporation rates in all types of solar desalination. The highest productivity of active solar still is belonged to ordinary black jute. Anthracite bed and nanoparticles has a high effect on freshwater yield of solar still. Hierarchical porous carbons increased the efficiency the system about 95%.